Fe(ClO4)3·H2O-Catalyzed Ritter Reaction: A Convenient Synthesis of Amides from Esters and Nitriles - Feng, Chengliang; Yan, Bin; Yin, Guibo; Chen, Junqing; Ji, Min (Synlett, 2018)
An efficient and inexpensive synthesis of N-substituted amides from the Ritter reaction of nitriles with esters catalyzed by Fe(ClO4)3·H2O is described. Fe(ClO4)3·H2O is an economically efficient catalyst for the Ritter reaction under solvent-free conditions. Reactions of a range of esters (benzyl, sec-alkyl, and tert-butyl esters) with nitriles (primary, secondary, tertiary, and aryl nitriles) were performed to provide the corresponding amides in high to excellent yields.
Keywords: Ritter reaction; Fe(ClO4)3·H2O; esters; nitriles; solvent-free reactions